Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2405685:2437EGZU
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7019219 ZenodoArchiveConcept: 7019218 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7019219 10.53832/edtechhub.0108 2339240:LNQBY8R8 2405685:49ZFP7UN 2405685:MP7LCGPN
Keywords: _r:AddedByZotZen

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8370318 ZenodoArchiveConcept: 8370317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8370318 10.53832/edtechhub.0175 2405685:XRGSHEUJ
Keywords: _r:AddedByZotZen

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10628960 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1011 ZenodoArchiveConcept: 10628959
Keywords: _r:AddedByMyEducationEvidence